A Bilingual Child’s Two Writing System - Lo, Yueh Yea (Society for Research and Knowledge Management, 2018)
The present study focusses on the writing evolution of a fourth-grade Japanese bilingual child who lives in Malaysia through the use of Howards' (2003) Two-Way Narrative Writing Assessment Rubric. This study examined the changes occurred in a bilingual child's journals written in Japanese and English, and to explore if there has been any interaction between his writing skills of the two languages. The data collection involved document analysis of his written journals. The document analysis of the written journals was based on word count, logography errors, and writing evolution (e.g., subject matter, sentence formation, and usage of adjectives). The findings of this study indicated that the participants' writing is grammatically correct in English, and both Japanese and English journals have a clear subject matter. However, further analysis on sentence formation and adjectives revealed that the participant has written poorly in his Japanese journals compared to his English journals. Thus, these findings point to the significance that schooling in two languages and early exposure of target language could have effectively supported the participant learning of writing skills. Through contrastive analysis, this study reflects on the successful evolution of bilingualism where it is possible for a bilingual child to acquire two different writing systems simultaneously.